Promoting Inclusivity and Multiculturalism: The Role of Muslim Scholars in Cape Town's Community Peacebuilding - Mohammed, Tawffeek; Al-Sowaidi, Belqes; Muhammed, Lubwama (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2024)
Religion plays a significant role in conflict prevention and peacebuilding, as demonstrated during the July 2021 riots in South Africa, when religious leaders actively contributed to reducing violence, particularly in KwaZulu-Natal. This study investigates the responses of Cape Town Muslim clerics and imams to the crisis through their sermons, focusing on their contributions to South Africa’s peacebuilding initiatives and the promotion of multiculturalism. Specifically, this study examines the Friday Nasiha (advice sermon) titled “Prayer Reflections on the Political Crisis of Our Country”, delivered by Imam Rashied Omer on Friday, 30 July 2021 (19 Dhul-Hijjah 1442) at the Claremont Main Road Mosque in Cape Town. Nasiha is analyzed within the framework of maqāṣid al-Sharīʿah (objectives of Islamic law) to evaluate its role in advancing peacebuilding efforts during the July 2021 unrest. Qualitative thematic analysis is used to explain how Islamic principles such as zakat (almsgiving) and ṣadaqah (charitable giving) address immediate socio-economic challenges and long-term structural justice. The findings underscore the role of religious leaders in times of conflict. The study concludes that Islamic teachings, when effectively applied in crisis situations, can significantly enhance peacebuilding efforts and support structural reforms in diverse societies.